Environmental sustainability of coffee farms in the Monzon valley - Huanuco - Caldas de la Cruz, Brayan André (2023)
The aim of the study was to determine the environmental sustainability of coffee farms in the Monzon Valley. The sample consisted of 56 coffee farms, of which 28 had a coffee agroforestry system and the other 28 had coffee monocultures. Indicators were used, which were standardized on a scale of 0 to 4.0. The coffee farms with a value higher than 2.0 are environmentally sustainable. It was found that agroforestry systems in the Monzon Valley at different altitudinal levels are environmentally sustainable, compared to coffee monocultures that are not. Highly significant differences were found between agroforestry systems and monocultures. In agroforestry systems, the sub- indicators crop diversification and plant biodiversity showed a significant correlation (r=0.470), while in monoculture, the sub-indicators soil cover management and soil conservation had a higher significant correlation (r=0.518). The use of coffee agroforestry systems contributes to maintaining a balanced environment in relation to monocultures that generate negative impacts on the environment.